Inner-biblical allusion in the poetry of Wisdom and Psalms - Boda, Mark J.; Chau, Kevin ca. 21. Jh.; Tanner, Beth LaNeel (Library of Hebrew Bible/Old Testament studies, 2019)
The Psalmist as historiographer / Jeffery M. Leonard -- Allusion or illusion in the Psalms : how do we decide? / Beth LaNeel Tanner -- Exodus 34.6 in Psalms 86, 103, and 145 in relation to the theological perspectives of Books III, IV, and V of the Psalter / Hee Suk Kim -- The elevation of God in Psalm 105 / David Emanuel -- The poetry of creation and victory in the Psalms / Kevin Chau -- A ridiculous God : Job uses Psalm 8.5 [4] to respond to Eliphaz / Charles Yu -- Poetic allusions in Agur's oracle in Proverbs 30.1-9 / Ryan P. O'Dowd -- The reuse of Deuteronomy's "Law of the vow" in Ecclesiastes 5.3-5 [4-6] as an exemplar of intertextuality and reinterpretation in Ecclesiastes 4.17-5.6 [5.1-5.7] / Richard L. Schultz -- Some reflections on interpreting allusion : the case of creation motifs in Isaiah / Job Y. Jindo.